Review of Bilateral Ties between India and Sri Lanka in the years after the Civil War: A Comprehensive Analysis of Post-Civil War Bilateral Ties between India and Sri Lanka (Journal of Advances and Scholarly Researches in Allied Education, 2021)
To the west, Sri Lanka has a close neighbor in India. Over the course of their more than 2,500-year-long history together, the two nations have exchanged ideas, culture, religion, and even language. Inrecent years, the two countries' leaders have met often, commerce and investment have increased, theywork together on matters of development, education, culture, and defense, and they have a common viewof the world's most pressing problems. The past year has seen increased bilateral exchanges between thetwo countries on a variety of levels, as well as significant advancements in the implementation ofdevelopmental assistance projects for the Internally Displaced Persons (IDPs) and disadvantagedsections of the population in Sri Lanka. In May 2009, the almost 30-year civil war between the Sri Lankangovernment and the LTTE was declared over. India stood for Sri Lanka's government, saying it had theright to use force against terrorists throughout the war. At the same time, it made clear at the highestlevels its concern for the condition of the mostly Tamil civilian population and the need to ensure thattheir rights and welfare were protected throughout the conflict with the LTTE. Is this paper discuss thebilateral ties between india and sri lanka in the years after the civil war.